Jezus za kaemem. Glossa z pogranicza literatury, teologii i historii sztuki - Zieliński, Jan (Colloquia Litteraria, 2013)
Machine Gun Jesus. A gloss between literature, theology and art history In order to explain a mysterious sentence in an article by Jerzy Stempowski on Józef Wittlin’s novel (published in the present issue of “CL”) about a sermon on Jesus at a German machine gun, the author makes a survey of several sermons delivered and published in protestant Switzerland during the First World War (including one by the future famous theologian Karl Barth). Another possible source for this phrase by Stempowski is an article published in 1930 in “Berliner Tageblatt” during a lawsuit for blasphemy against the painter George Grosz, the author of a drawing representing Jesus on the Cross with a gas mask. The gloss ends with some remarks on the later use of the terms “Machine Gun Jesus” or “God’s Machine Gun” (Johannes Leppich, Billy Graham, Ryszard Kapuściński, Sam Childers).